PENERAPAN MODEL PEMBELAJARAN KOOPERATIF THINK-PAIR-SHARE (TPS) BERBANTUAN MEDIA FLASH CARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KOSAKATA KELAS II SD NEGERI SOGO - Tho`ifah Ayu Firnanda; Saeful Mizan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The low understanding of second-grade students at SD Negeri Sogo in the Indonesian language subject is the main concern of this study. Preliminary observations indicate that the lack of creative and engaging teaching methods implemented by the teacher leads to students feeling bored and unmotivated. Although several variations of methods such as lectures and question-and-answer sessions have been applied, students remain passive listeners. Additionally, limitations in facilities and monotonous learning media, such as books and audiovisual aids, result in low student participation and enthusiasm. This research aims to implement the cooperative learning model of Think Pair Share (TPS) as a solution to enhance student involvement in the learning process. By providing opportunities for students to speak and express their ideas, this model is expected to motivate students to be more active. Furthermore, the use of engaging learning media, such as flash cards, is anticipated to improve students' interest and learning outcomes. Thus, this study aims to contribute positively to the enhancement of the quality of Indonesian language learning in the second grade at SD Negeri Sogo.